2017
DOI: 10.1371/journal.pone.0189583
|View full text |Cite
|
Sign up to set email alerts
|

Towards the identification of Idiopathic Parkinson’s Disease from the speech. New articulatory kinetic biomarkers

Abstract: Although a large amount of acoustic indicators have already been proposed in the literature to evaluate the hypokinetic dysarthria of people with Parkinson’s Disease, the goal of this work is to identify and interpret new reliable and complementary articulatory biomarkers that could be applied to predict/evaluate Parkinson’s Disease from a diadochokinetic test, contributing to the possibility of a further multidimensional analysis of the speech of parkinsonian patients. The new biomarkers proposed are based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 69 publications
1
42
0
3
Order By: Relevance
“…However, the sequence of syllables employed in the recordings (/pa-ta-ka/) contains only plosives. This fact can be explained by the inclination of many patients to replace plosives with fricatives [4], phenomenon (known as spirantization) which can be better detected with a classifier more influenced by the acoustic characteristics of fricatives or plosives.…”
Section: Databasementioning
confidence: 99%
See 1 more Smart Citation
“…However, the sequence of syllables employed in the recordings (/pa-ta-ka/) contains only plosives. This fact can be explained by the inclination of many patients to replace plosives with fricatives [4], phenomenon (known as spirantization) which can be better detected with a classifier more influenced by the acoustic characteristics of fricatives or plosives.…”
Section: Databasementioning
confidence: 99%
“…More recent works explore the automatic detection or assessment of PD by analyzing different types of segments of speech, the velocity or acceleration of articulators, specific transitions or the evolution of formants [2]- [4]. As an example, work [2] reports 80% of accuracy in PD detection using acoustic features extracted from only vowels in monologues.…”
Section: Introductionmentioning
confidence: 99%
“…Some preliminary findings suggest that this might be the case. For example, it has been found that voiced segments tend to be longer, while stop silences produced by the closures before bursts tend to disappear, in the speech of PD patients compared to control speakers 7,20 . These observations are in direct relationship with misarticulation phenomena common in some dysarthrias by which plosives are produced as fricatives, where the frication noise is not necessarily preceded by a closure.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, differences in the slopes and variability of the formant frequencies between patients and controls (and especially between the vowel space areas (VSA) of both groups) have been reported 21–27 . Based on that, recent studies propose automatic systems to detect or assess PD making use of the articulatory aspects of speech and advanced signal processing techniques, suggesting that speech processing can derive powerful indicators of imprecise consonant articulation in PD-related dysarthria 20,21,2830 . The accuracy in PD detection of these works, as in most of the works in the literature, does not exceed 90%, although it is difficult to compare the performance of the different methodologies since each study uses a different corpus and evaluates its results following a different procedure.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that changes in syllables is more difficult than repeating the same syllable. However, it was unexpected to see /ta/ on the list instead of /ka/ for Spanish speakers [25].…”
Section: Discussionmentioning
confidence: 99%